The Effect of the Third Severity Area of the Explosive Capacity of the two in the Performance of some Skills of the Artistic Gymnastics for Women (Journal of the College of Basic Education, 2024)
The aim of the research is to prepare exercises for the third intensity zone for the explosive power of the legs for women in the youth category in artistic gymnastics, and to identify the effect of exercises for the third intensity zone for the explosive power of the legs in performing the skills of jumping together on a horse, jumping openly on a horse, and rising to the balance beam using artistic gymnastics equipment for women. The experimental approach was adopted by designing the experimental and control groups, and the boundaries of the research community were represented by the athletes of the Sports Talent Care Center in gymnastics from the category of young women aged (15-17) years. For the sports season (2023-2024), they numbered (11) female players. They were deliberately selected using a comprehensive enumeration method, all of them (100%) from this population, and then they were randomly divided into two groups according to the experimental design, so that the first group was the experimental group with (5) female players, and the second group The second was controlled by a number of (6) female players, and the exercises were prepared, codified, and applied at a rate of (3) units per week for a period of (8) weeks. The research experiment began by applying the tribal skill tests with their visualizations for each of the female players of the two research groups on Thursday, corresponding to the date (11/1/2024). Then, the exercises under study are applied to the players of the experimental group, while the control group applies the followed exercises as they are for the period from Sunday, corresponding to the date (14/1/2024) until Thursday, corresponding to the date (7/3/2024), and completing this experiment by applying Post-tests on Sunday, (10/3/2024). After completing the research experiment, the results were processed with the SPSS system. The conclusions and recommendations were that preparing exercises for the third intensity zone for the explosive ability of the legs is suitable for young female athletes in the Center for Sports Talent Care in Appliance Gymnastics. The application helps in improving the technical performance of each of the jumping skills, including the vaulting horse, open jumping on the vaulting horse, and the skill of rising to the balance beam in apparatus gymnastics among female athletes who trained with them, and superior to those who trained without them. It is necessary, when training exercises in the third intensity zone for the explosive ability of the legs, to take into account the specificity of apparatus gymnastics and the need of young female athletes to adopt the scientific foundations of the principles of modern sports training in this planning and its appropriate training methods and methods to avoid fatigue or physical stress.